INNOVATIVE ENTREPRENEURSHIP IN UKRAINE: AXIOLOGICAL ASPECT - N. Ignatovych; V. Gura (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
The value descriptions of innovative entrepreneurship are considered. Nowadays it is a motive force of not only economy development but also the whole society. The important role of innovations in everyone’s life is shown. It is proved that innovations are also the means of survival for modern entrepreneurship in a changeable market environment. It is determined, that innovative activity is impossible without deep knowledge, scholarship and aspiration to improve quality of commodities, services, attain the put aims, realize a business-idea. It is researched, that passio adjusted people are able to initiate and carry out entrepreneurship innovative development. Important influence of spiritual, mental and ethical factors on entrepreneurs’ activity is analyzed. Absence of these factors in economic space during many years in Ukraine hasn’t resulted mass innovative character of entrepreneurship. It is established that for overcoming this situation it is necessary to appeal to the passionarity spiritual sources, use traditional national values. Domestic entrepreneurship must obtain necessary spiritual energy in an order to become the leading factor of the Ukrainian economy innovative development, to provide its modern modernization, to carry out a transition to postindustrial society.